Assessing the Use of Activated Carbon to Increase Biogas Production - Faith Wanadi Angeango (Uganda Christian University, 2024)
The enhancement of biogas production, specifically methane enrichment is critical for improving the efficiency and viability of biogas as a renewable energy source. This report examines the role of activated carbon in increasing methane yield and the quantity of biogas produced in a digester at NALIRRI by the Direct interspecies electron transfer Process (DIET). Activated carbon known for its high surface area, electrical conductivity and porosity provides a conducive environment for the adsorption of inhibitory compounds and the DIET process. Furthermore, it facilitates a more stable and enhanced microbial activity leading to increased biodegradation and methane production. Experimental setups incorporating various concentrations of activated carbon were monitored and analyzed. Parameters like pH, temperature and organic loading rate were monitored alongside the addition of activated carbon to maximize methane output. The results indicate a significant increase in methane production with the addition of activated carbon and it can contribute to the development of a cost-effective and sustainable method to increase the quantity of biogas produced in a bio-digester hence a promising approach to enhance biogas production with implications for renewable energy and waste management practices. This report concludes with recommendations for further research and application of biogas on systems.